MENUMBUHKAN PENGETAHUAN WAWASAN KEBANGSAAN DI ERA DIGITAL MELALUI KOMUNIKASI KEPADA WARGA DESA GUDANGKAHURIPAN KBB - Taufik, Cevi Mochamad; Fitriawati, Diny; Lusiawati, Ira; Ghassani, Rizqi; Bintang, Gilang; Fadilah, Dini Nur; Sabarudin, Didin; Aditya, Krisna; Wibowo, Edi; Sila, Gita Eka; Suldani , Muh. Resa Yudianto; Widyaputra , Fauzan Ahdi; et al. (JURNAL PENGABDIAN KEPADA MASYARAKAT (JPKM) KEBANGSAAN, 2025)
Attention to national values ​​and insight has almost disappeared among the majority of residents of Gudangkahuripan village, Lembang District, West Bandung Regency (KBB). In their daily lives, residents are more focused on meeting daily consumption needs than increasing and honing their knowledge of national insight. The only knowledge they ever acquired about national insight was during elementary and secondary school. After graduating, some continued on to college, while most focused on finding work. From that point on, they were almost no longer connected to national symbols and terms. Likewise, refresher courses on national values ​​and insight in the form of seminars, meetings, or discussions were almost never received. Starting from this condition, Community Service (PkM) lecturers and students of the Communication Science Study Program (Prodi Ilkom) of the National University of the Republic of Indonesia (UKRI) were directed to revitalize knowledge of national insight among the residents of Gudang Kahuripan village. The approach used was a lecture method by communicating the elements, components, mission and vision, and goals of nationality. PkM succeeded in raising awareness and interest among Gudangkahuripan villagers to trace the essence and identity as citizens of the nation. Awareness also occurs regarding the position of citizens as part of the digital world cycle.